Current situation of plastic producing companies in function of environmental preservation and conservation measures in the city of Guayaquil (Teorías, Enfoques y Aplicaciones en las Ciencias Sociales, 2020)
The purpose of any company that goes into operation is to obtain income, whether it is through the transformation of a good or service such as the distribution of a finished product, however, the form or conditions of transferring these goods to the final consumer , are affected by positive or negative external or internal factors that represent an increase or decrease in the profit obtained in each transaction; For the plastics sector, the city of Guayaquil, has demanded a particular consumption scheme, allowing the exclusive use of biodegradable materials or those that are easily returned to the production chain, once they have been used, therefore, generates a need for research for these companies or their early exit from the market. According to the data obtained from the plastic companies located in the city, their profitability has been affected in recent years when this regulation was imposed, which means adding one more variable to the conditions to compete in this type of market.
Keywords: plastic; biodegradable; benefit; companies; Guayaquil